COGENERATION DEVICE BASED ON INNOVATIVE TECHNOLOGY ORGANIZATION OF ORGANIC WASTE - KOSIYUK, Mykola (Herald of Khmelnytskyi National University. Technical sciences, 2022)
This work considers the issue of creating efficient and environmentally friendly energy systems based on cogeneration technology. In industrialized countries, work is underway to develop and implement innovative technology for supercritical hydrothermal destruction of industrial and household waste and highly toxic substances. An extremely important urgent task is the complex solution of the problems of creating an autonomous energy complex based on the technology of cogeneration and utilization of organic waste and their use as renewable energy sources. Theoretical and experimental studies have shown that the method of supercritical hydrothermal destruction has high environmental and economic efficiency and demonstrates versatility, providing complete one-stage disposal of any organic waste. It is established that the reaction of supercritical aqueous oxidation of organic matter is exothermic and in the presence of only 15-20% of organic matter the waste processing process becomes autothermal.Autothermal modes of destruction of organic waste at supercritical parameters of the aquatic environment lead to a high-enthalpy vapor-gas mixture, which can be used in the schemes of the autonomous energy complex. Cogeneration units are offered on the basis of a steam power plant operating on the Rankin cycle and on the basis of a heat engine with external heat supply, which operates on a closed thermodynamic Stirling cycle. A non-standard equipment of supercritical hydrothermal destruction technology is a quasi-flow reactor. The conducted research testifies to the possibility of further development of supercritical hydrothermal destruction technologies, both in terms of providing increased process parameters and in terms of developing increasingly reliable, productive and safe types of reactors. The development is based on the replacement of a single-pipe coaxial (two-pipe) reactor. This reactor design significantly expands the temperature and barometric performance characteristics, allows to increase the heat transfer surface and the temperature inside the reactor, bringing it closer to the external temperature of the reactor wall surface while maintaining performance. The cogeneration unit can be used to solve energy efficient and environmentally friendly disposal of organic waste. Allows to solve problems of autonomous electricity and heat supply of industrial and residential facilities and has significant market potential.
Keywords: heat energy; energy efficiency; cogeneration; renewable energy sources; supercritical state of water; destruction; oxidation